Training Health Cadres in Overcoming Nausea, Vomiting, and Sleep Disorders - Wijayanti, Lono; Purwanti, Nunik; Septianingrum, Yurike; Damawiyah, Siti (Universitas Malahayati Lampung, 2025)
ABSTRACT Nausea, vomiting, and sleep disorders are common complaints often experienced by the community, especially among vulnerable groups such as the elderly and patients with chronic diseases. If not treated properly, these conditions can reduce quality of life and increase the risk of complications. Health cadres, as the spearhead of health services in the community, have a strategic role in the early detection and initial treatment of these complaints. This training activity aims to improve the knowledge and skills of health cadres in recognizing, preventing, and managing nausea, vomiting, and sleep disorders appropriately and in a community-based manner. The training methods include interactive lectures, simulations, and case discussions. Evaluation results show a significant improvement in cadres' understanding of the training material and their practical ability to provide education and initial intervention to the community. It is hoped that this activity will strengthen the capacity of cadres in supporting public health programs, particularly in promotive and preventive efforts related to nausea, vomiting, and sleep disorders. Keywords: Health Cadres, Nausea And Vomiting, Sleep Disturbances, Promotive-Preventive